Metal nanoparticles and nanoalloys - Johnston, R. L. (Roy Luigi); Wilcoxon, J. P. (Jess P.) (Frontiers of nanoscience, 2012)
The field of nanoscience has undergone tremendous growth in the past decade as the number of applications of nanoparticles and nanostructured materials have proliferated. Metal nanoparticles have attracted particular interest due to their versatility of application in areas as diverse as catalysis, medicine and opto-electronics. A unified discussion of the inter-relations between modelling, synthesis and physical properties of nanoparticles and nanoalloys A discussion of the most promising new catalytic and photocatalytic applications of nanoparticles and the approaches used to achieve these goals A tutorial introduction which provides a basis for understanding the subsequent specialized chapters.